2007
DOI: 10.1007/s10661-007-9778-z
|View full text |Cite
|
Sign up to set email alerts
|

Residues of organochlorine pesticides in water and suspended particulate matter from the Yangtze River catchment of Wuhan, China

Abstract: The residues of 13 organochlorine pesticides (OCPs) in surface water and HCHs and DDTs in suspended particulate matter (SPM) from rivers and lakes in Yangtze River catchment of Wuhan, China, were investigated. The concentration of total OCPs in surface water varied from 1.01 to 46.49 ng l(-1) (mean 10.55 ng l(-1)). The levels of total HCHs (SigmaHCH) and total DDTs (SigmaDDT) in surface water were in the range of 0.55-28.07 ng l(-1) and lower than detection limit to 16.71 ng l(-1), respectively, which was lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 37 publications
(38 reference statements)
3
35
2
Order By: Relevance
“…To understand the current contamination status of OCPs in the study areas, the concentrations of OCPs measured in surface water of Lake Taihu were compared with the results from other surface waters (Table 2). As seen in Table 2, the concentrations of individual OCPs in Lake Taihu (this study) were lower than those reported in Minjiang River (Zhang et al 2003), Qiantang River , Tonghui River (Zhang et al 2004), Lake Xihu (Liang et al 2008), Jiulongjiang River (Zhang et al 2001), Liaohe River , Daliaohe River (Li et al 2009), Suzhouhe River (Hu et al 2005), Pearl River (Yang et al 2004), Yangtze River (Tang et al 2008), Haihe River (Wang et al 2007), and Guangting Reservoir-Yongding River (Kang et al 2003) in China. The average concentrations of γ -HCH and DDTs were found to be lower in Lake Taihu in this study than the previous study conducted by Ta et al (2006).…”
Section: Environmental Concentrations Of Ocpscontrasting
confidence: 49%
“…To understand the current contamination status of OCPs in the study areas, the concentrations of OCPs measured in surface water of Lake Taihu were compared with the results from other surface waters (Table 2). As seen in Table 2, the concentrations of individual OCPs in Lake Taihu (this study) were lower than those reported in Minjiang River (Zhang et al 2003), Qiantang River , Tonghui River (Zhang et al 2004), Lake Xihu (Liang et al 2008), Jiulongjiang River (Zhang et al 2001), Liaohe River , Daliaohe River (Li et al 2009), Suzhouhe River (Hu et al 2005), Pearl River (Yang et al 2004), Yangtze River (Tang et al 2008), Haihe River (Wang et al 2007), and Guangting Reservoir-Yongding River (Kang et al 2003) in China. The average concentrations of γ -HCH and DDTs were found to be lower in Lake Taihu in this study than the previous study conducted by Ta et al (2006).…”
Section: Environmental Concentrations Of Ocpscontrasting
confidence: 49%
“…These levels are nearly same as the Yangtze River (0.55-28.07 ng/L) (Tang et al, 2008) and the Liaohe River (6.19-35.19 ng/L) (Gawlik et al, 2000), higher than the Huihe River (0.47-6.13 ng/L) (Feng et al, 2011), but lower than the Qiantang River (0.74-543.1 ng/L) (Zhou et al, 2008). When compared with other rivers over the world, concentration of HCHs in water from the Jinjiang River was similar to that of the Nestos River, Greek (n.d. À 68.00 ng/L) (Golfinopoulos et al, 2003) and much lower than the Giomti River, India (0.02-4846.00 ng/L) (Singh et al, 2005) and the Kucuk Menderes River, Turkey (187.00-337.00 ng/L) (Turgut, 2003).…”
Section: Ocps In Surface Water Of the Jinjiang Rivermentioning
confidence: 63%
“…∑DDT concentrations in surface water samples were higher than that in Ebro River, Spain (3.40 ug/L) (Fernandez et al, 1999), while lower than those in the Yangtze River (nd-16.71 ug/L) (Tang et al, 2008), Huaihe River (4.44-33.59) (Feng et al, 2011) and Nestos River, Greece (nd-64.00 ug/L) (Golfinopoulos et al, 2003), and much lower than those in the Qiantang River (nd-204.1 ug/L) (Zhou et al, 2006), Gomti River, India (0.20-4578.00 ug/L) (Malik et al, 2007), and Kucuk Menderes River, Turkey (72-120 ug/L) (Turgut, 2003).…”
mentioning
confidence: 70%
“…∑HCH concentrations of the 29 surface water samples were higher than those in Peacock River, Xin Jiang Province (nd-19.00 ug/L) (Chen et al, 2011) and Huaihe River (0.47-6.13 ug/L) (Feng et al, 2011), while lower than those in the Yangtze River (0.55-28.07 ug/L) (Tang et al, 2008), Qiantang River (0.74-543.1 ug/L) (Gong et al, 2004a,b), Nestos River, Greece (nd-68.00 ug/L) (Golfinopoulos et al, 2003) and much lower than those in the Gomti River, India (0.02-4846.00 ug/L) (Malik et al, 2007) (Table 4). ∑DDT concentrations in surface water samples were higher than that in Ebro River, Spain (3.40 ug/L) (Fernandez et al, 1999), while lower than those in the Yangtze River (nd-16.71 ug/L) (Tang et al, 2008), Huaihe River (4.44-33.59) (Feng et al, 2011) and Nestos River, Greece (nd-64.00 ug/L) (Golfinopoulos et al, 2003), and much lower than those in the Qiantang River (nd-204.1 ug/L) (Zhou et al, 2006), Gomti River, India (0.20-4578.00 ug/L) (Malik et al, 2007), and Kucuk Menderes River, Turkey (72-120 ug/L) (Turgut, 2003).…”
mentioning
confidence: 73%
See 1 more Smart Citation